Emotion regulation choice: the role of orienting attention and action readiness. (February 2018) - Ghafur, Reza D; Suri, Gaurav; Gross, James J
Highlights: Depending on the circumstances, some emotion regulation strategies are more adaptive than others. People do not always make optimal emotion regulation (ER) decisions. Increasing orienting attention toward using better ER strategies will lead to better outcomes. It is helpful to increase action readiness for implementing adaptive ER strategies. Leveraging the interaction of attention and readiness might lead to novel ER interventions. Abstract : People frequently do not regulate their emotions even when doing so would be adaptive. Further, people often use maladaptive emotion regulation strategies, despite knowledge of more adaptive strategies. We propose that such anomalies can be explained at least in part by the orienting attention/action readiness (OAAR) framework according to which people are more likely to implement a particular emotion regulation strategy when (1) they direct a sufficient level orienting attention towards initiating it, and/or (2) they have a sufficient level of action readiness with respect to that strategy because they have recently/frequently implemented it in similar contexts. We provide evidence for the OAAR framework and discuss how it might be leveraged to promote more effective regulation of undesirable emotions.